One case report of thin basement membrane nephropathy with heavy proteinuria and literature review - ZHANG Dan-dan; LI Jun-hua; YAO Ying (Linchuang shenzangbing zazhi)
Objective To explore diagnosis,treatment and prognosis of thin basement membrane nephropathy with heavy proteinuria so as to improve the understanding of the disease,and get the correct and reasonable treatment early. Methods The clinical data of one case were analyzed retrospectively,in which the heavy proteinuria and hematuria were the patient ’s manifestation. Heoral Huang Kwai capsule,dipyridamole tablets,compound kidney inflammation tablets were orally administered for several months,but the treatment is invalid. The kidney puncture biopsy pathological examination revealed the diagnosis of thin basement membrane nephropathy. According to the above clinical data we summarized literatures. Results Glucocorticoid treatment was given for one year,and proteinuria and hematuria were negative. Conclusions Althou ghematuria was its predominant finding,TBMN also manifested heavy proteinuria,even nephrotic syndrome,and had good response to hormone therapy.